2011
DOI: 10.2223/jped.2115
|View full text |Cite
|
Sign up to set email alerts
|

Association of air pollution and hematologic parameters in children and adolescents

Abstract: Objective: To assess the relationship of air pollution and hematologic parameters in a population-based sample of children and adolescents. Methods:This cross-sectional study was conducted in 2009-2010 among school students randomly selected from different areas of Isfahan city, the second largest and most air-polluted city in Iran. The association of air pollutants levels with hemoglobin, platelets, red and white blood cells (RBC and WBC, respectively) levels was determined by multiple linear and logistic reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 30 publications
1
21
1
Order By: Relevance
“…In addition, several other studies report effects on WBC counts after exposure to lower doses of air pollution (Table 1). Some observed increases in total WBC or neutrophil counts (Frampton et al, 2004;Jacobs et al, 2010;Poursafa et al,2011;Riediker et al, 2004;Salvi et al, 1999;Schwartz, 2001;Tan et al, 2000), whereas others found decreases in total WBC, neutrophil or monocyte counts (Ghio et al, 2003;Rich et al, 2012;Rückerl et al, 2007;Zuurbier et al, 2011). Because of major differences in study design (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, several other studies report effects on WBC counts after exposure to lower doses of air pollution (Table 1). Some observed increases in total WBC or neutrophil counts (Frampton et al, 2004;Jacobs et al, 2010;Poursafa et al,2011;Riediker et al, 2004;Salvi et al, 1999;Schwartz, 2001;Tan et al, 2000), whereas others found decreases in total WBC, neutrophil or monocyte counts (Ghio et al, 2003;Rich et al, 2012;Rückerl et al, 2007;Zuurbier et al, 2011). Because of major differences in study design (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Children appear to be more vulnerable than adults to the adverse health effects of PM and other air pollutants because of their smaller airways and lung size, increased baseline ventilation rates, propensity to mouth breathe, and greater time spent running, jumping, and other aerobic play activities which expose them to greater pollutant loads penetrating deeper into lung tissues (Wright and Brunst, 2013; Bateson and Schwartz, 2008). It is indicative that higher exposure to urban air pollutants is associated with increased blood markers of oxidative stress, systemic inflammation, and endothelial dysfunction in children (Wu et al, 2015; Calderon-Garciduenas et al, 2009; Kelishadi et al, 2014; Poursafa et al, 2011). …”
Section: 0 Introductionmentioning
confidence: 99%
“…Furthermore, air pollutants can provoke systemic proinflammatory and pro-thrombotic response and lead to increase in platelet counts and platelet activation (122). The significance of platelet activation and whether anti-platelet therapies can help reducing cardiovascular risk profiles in the youth populations is still a debatable subject (123). Further studies are required to examine the impact of heavy metals and environmental pollutants, as novel cardiovascular risk factors, in accelerating the development of cardiovascular disease in both adults and the youth populations(124).…”
Section: Heavy Metals and Environmental Pollutantsmentioning
confidence: 99%